Dynamics Analysis of Needle Rod Mechanism of Tufting Carpet Machine based on ADAMS - Li Dinglin; Xu Yang (Jixie chuandong)
The tufting carpet machine has multiple sets of linkage mechanism,and the movement of the linkage mechanism directly affect the quality of the weaving and efficiency of the loom. Taking the needle rod mechanism of tufting carpet machine as the research object,by using ADAMS simulation software,a simple model of tufting carpet machine needle rod mechanism is built and the dynamics simulation analysis is carried out. The diagram of reaction of supports,working retard moment and the balance torque on the crank of each connection point on the crank- rocker mechanism of the tufting needle rod mechanism is obtained. And comparing with the diagram of experimental data which is by numerical analysis that to verify the correctness of the dynamic simulation analysis,and a basis for the optimization design of tufting needle rod mechanism is provided.